Representation of indigenous peoples in times of progressive governments: lessons learned from Bolivia. Issue 2 (3rd April 2022) - Barié, Cletus Gregor
ABSTRACT: Indigenous peoples in Latin America are historically underrepresented in elected bodies. In 2009, Bolivia introduced a new mechanism for direct representation to counteract this systematic representation gap, securing 7 of 130 seats (5.4%) in the national parliament for indigenous peoples of the lowlands. The reform was part of a series of implementation conflicts related to a new vision of plurinational state-building, included in the new 2009 Constitution. Although most indigenous organizations were seeking a 'power-sharing' agreement with direct representation for all indigenous nations, the new government, led by President Evo Morales, successfully intervened in favor of a minority protection scheme. Furthermore, for the direct representatives, the room to maneuver left was severely limited, leaving little space to act on behalf of their minority constituencies. Curiously, this reduced version of direct representation is nonetheless the most advanced in Latin America. The Bolivian case provides important lessons on the 'de-monopolization' of political parties as a key factor in the effective representation of indigenous peoples in parliament, as well as on the importance of a goal-oriented design for electoral mechanisms focusing on substantive representation.